2017
DOI: 10.1126/science.aal3118
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing dynamic microvillar search and stabilization during ligand detection by T cells

Abstract: During immune surveillance, T cells survey the surface of antigen-presenting cells. In searching for peptide-loaded major histocompatibility complexes (pMHCs), they must solve a classic trade-off between speed and sensitivity. It has long been supposed that microvilli on T cells act as sensory organs to enable search, but their strategy has been unknown. We used lattice light-sheet and quantum dot-enabled synaptic contact mapping microscopy to show that anomalous diffusion and fractal organization of microvill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
274
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(301 citation statements)
references
References 35 publications
18
274
3
Order By: Relevance
“…We found that at both temperatures L-selectin was concentrated on microvilli, 1,2 while CD45 was distributed uniformly throughout the membrane. 1,4,5 Next, we stained T cells with Alexa-647 labelled anti human TCRαβ antibodies at the two temperatures. At 4°C the structure of microvilli on almost all the T cells was intact, and the TCRαβ molecules localized on them (Fig.…”
Section: Supporting Textmentioning
confidence: 99%
“…We found that at both temperatures L-selectin was concentrated on microvilli, 1,2 while CD45 was distributed uniformly throughout the membrane. 1,4,5 Next, we stained T cells with Alexa-647 labelled anti human TCRαβ antibodies at the two temperatures. At 4°C the structure of microvilli on almost all the T cells was intact, and the TCRαβ molecules localized on them (Fig.…”
Section: Supporting Textmentioning
confidence: 99%
“…Another 3D lightsheet microscopy example involves tracking dozens of T-cell surface protrusions used to interrogate antigen presenting cells 21 . Again, VR is well suited to the task by combining stereo perception and hand-controlled time series playback to manually track paths of individual protrusions, determine their lifetimes, and assess localization of fluorescently labeled T-cell receptors seen in a second channel (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple models that attempt to relate T-cell function with the organization of receptors on the cell surface treat the plasma membrane as a 2-D sheet, rather than a 3-D surface (14-18, 20, 48). Recent studies have begun to unearth the pivotal role of microvilli as sensors involved in the initial stages of the immune response (11,12,27,28). In this work we investigated the properties of microvilli that makes them effective sensors.…”
Section: Discussionmentioning
confidence: 99%
“…4B) also pointed to a homogeneous distribution of the CD45 molecules all over the membrane. Interestingly, two recent studies also demonstrated a uniform distribution of CD45 on the T-cell membrane (27,45).…”
Section: Lat (Linker For Activation Of T Cells) This Adaptor Proteinmentioning
confidence: 94%
See 1 more Smart Citation